The Influences of Chemical Composition Upon the Hardness and Stability of Prothetic Restoration Materials - Adrian Dorin Cherciu Ciobotaru; Adina Oana Armencia; Maria Ursache (Romanian Society of Oral Rehabilitation, 2011)
The aim of the study was the - reducing and complex character upon the hardness of Ni-Cr alloy covered with ceramics. Matherial and method: ed into sterilized containers with artificial saliva (sterilized by autoclaving for 30 min., 1 atm) in saliva-alloy weight ratio: 15 / 1. The second solution is used electrolyte-matrix synthetic artificial saliva in the pH range 2-8, in the presence of oxalate and tartrate ions with oxidation-reduction and complex character, the ionic strength of 35-45 mmol / L. pH corrections were done with NaHCO3, CH3COONa and HCl, while the ionic strength correction was performed with buffer TISAB (Total Ionic Strength Buffer Adjudment) composed of NaCl and CH3COOH CH3COONa. Samples were collected every 15 days electrolyte and alloy elements concentration was determined by spectrometry with atomic absorption with flame (Faas type Perkin Elmer 3300) and potentiometers with SMEI (ion-selective membrane electrode-type pH-Ion-Meter OP-202-RADELKIS). Results: Micro hardness variation is visible (in cross section) depending on the layer studied. In the Plate, the average micro hardness values is quite small (285.8 GPa for a variation of micro hardness between 288-321 GPa), but as we approach the ceramic layer micro hardness gradually increases (reaching values about 987 GPa). Aluminium is currently heavily corroded due to higher electronegativity values of Cu (Cu = 1.8, Al = 1.5) and more positive standard potential of Cu (Cu 0.33 V, Al = -1.66 V). Tin is passive at pH 2-4, and at pH = 8. Nickel is turn passive at pH = 7 and dissolve at a pH = 2-6. Molybdenum is active at pH 2-4. Iron and cobalt are active at pH 2-4 and at pH = 9 passive. All these chemical reactions alter the surface quality of the alloy, with increasing surface roughness and finally compromise-to-end the resistance of restorative material. Increasing the concentration of silicon (where the ceramic material is used) increases the rate of galvanic corrosion due to the effect of Si. Conclusions: A restorative material used for the purpose of micro hardness and resistance varies depending on the type of electrolyte is introduced.